Implementation Of Kumon Learning Method To Student Learning Independence - Rachmawati Putri (Pancaran Pendidikan, 2017)
Mathematics is an exact science or science of certain knowledge about the logic of the form, order, scale, and concepts that are related to each other. In mathematics teaching, the understanding of the concepts of the essential very important. The understanding of the concepts of the essential that both will make the students put the concepts of the concept in the long-term memory system and can use them to think on a higher level thinking such as problem-solving and creative thinking. The understanding of the concepts of the essential that will aid them in reaching the specified minimum value in formal education. But in fact, many students who are still far from the ideal condition. The understanding of essential concepts in mathematics for material operation count is still low. In addition the number of students who successfully reach and exceed the minimum value formal education less than 70%. This is what causes the number of teachers must perform a remedial learning classical. Not yet on the actual condition, many students who are not able to follow the lessons but can still up the class seems to get "values" mercy from the teachers. If things like this continue to happen, then their understanding will not be formed as a whole to be able to continue teaching on the next material that the fact of the matter is the lesson materials that more complex. The Kumon Method is a unique educational method, which does not generalize the ability of each student. Based on individual guidance and learning at the right level, Kumon wants to develop each child's ability and maximize its potential. Kumon appreciates the value of independent learning.  Thus, individual guidance is one of the basic features of the Kumon Method. The key to an individual guidance is learning at the right level when students can advance independently without being specifically taught. With the Kumon Method, students learn independently from an early age and develop both a high level of academic ability and the ability to learn independently or in  Kumon better known as the  "ability to learn independently". Individual guidance Kumon method allows each student to learn at levels that best suit their academic ability, regardless of age or level of schooling, and to advance beyond the current school levels.